Statistics in engineering : with examples in MATLAB and R /: with examples in MATLAB and R. ([2019]) - Metcalfe, Andrew V; Green, David (David A.); Greenfield, Tony; Mansor, Mahayaudin (Mahayaudin M.); Smith, Andrew (Andrew G.); Tuke, Jonathan
No abstract available